Análise hidrológica experimental de lotes urbanos sob formas diferenciadas de ocupação e controle da inundação - Campos, João Batista Neto de (Universidade Federal de São Carlos, 2006)
The all-purpose of the present paper is to evaluate the hydrological behavior of some real experimental lots of different uses and occupation. For trial, three pilot urban lots were implanted in real scale and measuring 12 (twelve) meters front by 30 (thirty) meters depth each one, reproducing the urban standard characters of coast side of Bertioga / São Paulo. One lot was kept in natural conditions, with no edification; another one got 75% of its area, related to floor and edification, waterproofed, called common lot. The third one, identical to the conventional lot and called sustainable, got two microreservoirs (with total useful volume of 1,5m³) installed on its inside. The lots were grounded elevating their land level on 0,6m, and the lots soil and grounding characterized on their granulometria. The precipitation was continuously recorded, minute by minute, with a pluviograph installed on central lot. The effluent outflows were individually measured with a triangular spillway with fine walls, lab calibrated. The visual analysis of the hydrograms concludes that the convencional lot responds much faster than others, for its greater outflow peeks and smaller ascending time. The presence of micro reservoir on sustainable lot has considerably reduced outflows related to conventional one, with a consequently sensible reduction of outflowing coefficient of superficial outflow average of 0,72 (conventional lot) to 0,10 (sustainable lot). The delay time of conventional lot was mostly third part of sustainable lot s time because of micro reservoirs effect.
Keywords: Inundação; Ocupação do solo; Precipitação; ENGENHARIAS::ENGENHARIA CIVIL